Noninvasive staging of pressure ulcers using photoacoustic imaging. Issue 5 (26th July 2019) - Hariri, Ali; Chen, Fang; Moore, Colman; Jokerst, Jesse V.
ABSTRACT: Ulcers including pressure ulcers and diabetic foot ulcers damage the skin and underlying tissue in people with compromised blood circulation. They are classified into four stages of severity and span from mild reddening of the skin to tissue damage and muscle/bone infections. Here, we used photoacoustic imaging as a noninvasive method for detecting early tissue damage that cannot be visually observed while also staging the disease using quantitative image analysis. We used a mouse model of pressure ulcers by implanting subdermal magnets in the dorsal flank and periodically applying an external magnet to the healed implant site. The magnet‐induced pressure was applied in cycles, and the extent of ulceration was dictated by the number of cycles. We used both laser‐ and light‐emitting diode (LED)‐based photoacoustic imaging tools with 690 nm excitation to evaluate the change in photoacoustic signal and depth of injury. Using laser‐based photoacoustic imaging system, we found a 4.4‐fold increase in the photoacoustic intensity in stage I vs. baseline (no pressure). We also evaluated the depth of injury using photoacoustics. We measured a photoacoustic ulcer depth of 0.38 ± 0.09 mm, 0.74 ± 0.11 mm, 1.63 ± 0.4 mm, and 2.7 ± 0.31 mm ( n = 4) for stages I–IV, respectively. The photoacoustic depth differences between each stage were significant ( p  < 0.05). We also used an LED‐based photoacoustic imaging system to detect early stage (stage I) pressure ulcers and observed a 2.5‐fold increase in photoacoustic signal. Importantly, we confirmed the capacity of this technique to detect dysregulated skin even before stage I ulcers have erupted. We also observed significant changes in photoacoustic intensity during healing suggesting that this approach can monitor therapy. These findings were confirmed with histology. These results suggest that this photoacoustic‐based approach might have clinical value for monitoring skin diseases including pressure ulcers.